Importance of Low Humidity and Selection of Halide Ions of Octylammonium Halide in 2D–3D Perovskite Solar Cells Fabricated in Air. Issue 10 (3rd March 2023) - Kwon, Su Yeon; Kang, Byungsoo; Won, Jong Hyeon; Lee, Chae Young; Hwang, Kahee; Kim, Hong Hee; Park, Donghee; Choi, Won Kook; Kim, In Soo; Kim, Gee Yeong; Jang, Yoon Hee; Lee, Phillip; et al.
Abstract: Air fabrication of efficient and stable perovskite solar cells with substantial reproducibility is of importance for commercialization of perovskite solar cells. There has been little consensus on which halide is the best selection for thin 2D perovskite layer on 3D perovskite when processing in ambient air. In this work, the influence of humidity and halide ions in alkylammonium halide (OAX)‐treated perovskite layer on photovoltaic performance is investigated. The authors find that a combination of high humidity and the presence of chloride ions can induce the deprotonation of methylammonium (MA + ) ions. With X‐ray diffraction, cross‐sectional scanning electron microscope, Fourier‐transform infrared spectroscopy, the authors elucidate that the deprotonation reaction in the octylammonium chloride (OACl)‐treated perovskite layer makes MA + ions (CH3 NH3 + ) volatile MA (CH3 NH2 ), which results in void volumes and defects in the bulk of perovskite layer as well as at the interface. The defective perovskite solar cells induced by the deprotonation reaction have the suppressed hole transfer at the interface between the perovskite layer and the hole transport layer, yielding the reduced internal quantum efficiency and J SC . Space charge‐limited current analysis reveals that the reduced V OC is caused by the high trap density estimated from V TFL of hole‐only devices. Abstract : The present study investigates the influence of humidity and halide ions in 2D–3D perovskite layer on photovoltaic performance. A combination of high humidity and chloride ions induces the deprotonation of organic ammonium cations leading to defects formation. The defective perovskite solar cells have the suppressed hole transfer, low internal quantum efficiency, and the trap‐assisted recombination.